Synchronization of chaotic delayed systems via intermittent control and its adaptive strategy - Liu, Mei; Chen, Jie; Jiang, Haijun; Yu, Zhiyong; Hu, Cheng; Lu, Binglong (Nonlinear Analysis: Modelling and Control, 2021)
In this paper the problem of synchronization for delayed chaotic systems is considered based on aperiodic intermittent control. First, delayed chaotic systems are proposed via aperiodic adaptive intermittent control. Next, to cut down the control gain, a new generalized intermittent control and its adaptive strategy is introduced. Then, by constructing a piecewise Lyapunov auxiliary function and making use of piecewise analysis technique, some effective and novel criteria are obtained to ensure the global synchronization of delayed chaotic systems by means of the designed control protocols. At the end, two examples with numerical simulations are provided to verify the effectiveness of the theoretical results proposed scheme.